2014
DOI: 10.1002/jee.20036
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Instrument to Measure Leadership, Change, and Synthesis in Engineering Undergraduates

Abstract: Background Studies have highlighted the importance for engineers of leadership, adaptability to change, and synthesis of multiple perspectives. Yet only a few studies and instruments have explored the operational definitions of these concepts for engineering undergraduates.Purpose The goals of this research were to identify observable outcomes that engineering undergraduate students should demonstrate related to leadership, adaptability to change, and synthesis abilities and to create an instrument to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 51 publications
(26 reference statements)
1
60
0
1
Order By: Relevance
“…It is clearly stated that leadership is not orthogonal to the remainder of the engineering curriculum, but rather there is an extensive amount of overlap between leadership skills and the other engineering skills 9 . More study operationalized leadership, change, and synthesis within the context of engineering education, it may help to define learning outcomes and competencies for engineering leadership programs 3,10 .Some research grouped three main themes from the perspective of engineering students, academics, and professionals: Strong Character, Team Dynamics and Technical 11 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clearly stated that leadership is not orthogonal to the remainder of the engineering curriculum, but rather there is an extensive amount of overlap between leadership skills and the other engineering skills 9 . More study operationalized leadership, change, and synthesis within the context of engineering education, it may help to define learning outcomes and competencies for engineering leadership programs 3,10 .Some research grouped three main themes from the perspective of engineering students, academics, and professionals: Strong Character, Team Dynamics and Technical 11 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is actually happening in the data 17 ? In the fourth phase of analysis, relationships between the categories were examined and then collapsed under a construct (higher-level category) that explained most of the variation in the data 3 .…”
Section: Phase I: Identifying Definition Of Engineering Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of personalized assessment tools incorporated in the program to assess whether engineering leadership courses are meeting desired outcomes. A thorough literature review showed that although a survey had been developed for individual assessment of leadership qualities 1 , there was no instrument to assess its results and provide engineering students with comprehensive feedback in comparison to their peers and provide them with actionable feedback regarding their leadership efforts. This paper introduces a way to translate the empirical results of the engineering leadership survey into a personalized leadership profile that helps students to identify potential areas of leadership improvement by comparing their individual responses to large group responses informed from a previous study 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A thorough literature review showed that although a survey had been developed for individual assessment of leadership qualities 1 , there was no instrument to assess its results and provide engineering students with comprehensive feedback in comparison to their peers and provide them with actionable feedback regarding their leadership efforts. This paper introduces a way to translate the empirical results of the engineering leadership survey into a personalized leadership profile that helps students to identify potential areas of leadership improvement by comparing their individual responses to large group responses informed from a previous study 1 . Following a brief introduction of Purdue University's Engineering Leadership Minor and a description of the survey instrument used for personal leadership monitoring, the methods section describes how individual leadership profile Page 26.632.2 scores were calculated, and presents sample individualized student reports and recommendations provided to guide students toward relevant engineering leadership coursework.…”
Section: Introductionmentioning
confidence: 99%